2012
DOI: 10.1136/bmjqs-2012-001011
|View full text |Cite
|
Sign up to set email alerts
|

Building a culture of safety through team training and engagement

Abstract: Medical errors continue to occur despite multiple strategies devised for their prevention. Although many safety initiatives lead to improvement, they are often short lived and unsustainable. Our goal was to build a culture of patient safety within a structure that optimised teamwork and ongoing engagement of the healthcare team. Teamwork impacts the effectiveness of care, patient safety and clinical outcomes, and team training has been identified as a strategy for enhancing teamwork, reducing medical errors an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
118
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(127 citation statements)
references
References 24 publications
5
118
0
4
Order By: Relevance
“…A large body of published work showed the success of such training in achieving improved skills and reduced errors in such varied settings as neonatal units, long-term care facilities, and general hospitals, and with student health-care professionals. [334][335][336] The application of teambased education for the care of patients with cancer in primary care is a promising approach that builds on the increasingly interprofessional make-up of primary care services in many countries.…”
Section: Oncology Training In Medical Educationmentioning
confidence: 99%
“…A large body of published work showed the success of such training in achieving improved skills and reduced errors in such varied settings as neonatal units, long-term care facilities, and general hospitals, and with student health-care professionals. [334][335][336] The application of teambased education for the care of patients with cancer in primary care is a promising approach that builds on the increasingly interprofessional make-up of primary care services in many countries.…”
Section: Oncology Training In Medical Educationmentioning
confidence: 99%
“…The Hospital Survey on Patient Safety Culture (HSOPSC) of the AHRQ was applied before and after programme implementation to compare the perceptions of the staff on patient safety. The results showed significant improvements (17) . Another study conducted TeamSTEPPS training with 306 students of medicine, nursing, pharmacy and medical assistants.…”
Section: Discussionmentioning
confidence: 68%
“…The Department of Defense Patient Safety Program in collaboration with the Agency for Healthcare Research and Quality (ARHQ) created the programme Team Strategies and Tools to Enhance Performance and Patient Safety (TeamSTEPPS), which is a system of teamwork based on evidence to improve the communication and teamwork skills of health professionals (17)(18) . Studies have been conducted using this programme to ascertain its eff ectiveness and benefi ts for patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…Research with TeamSTEPPS has demonstrated its effectiveness in developing and maintaining superior team performance and effectiveness in diverse health care settings. 74,75 Global mindset refers to how we think about globalization. At the individual level, global mindset refers to an individual leader's comfort with multiple cultural influences.…”
Section: Global Leadership Developmentmentioning
confidence: 99%